A Public-Private Partnership to Locate Fields for Implementation and Monitoring of Best Management Practices to Treat Legacy Phosphorus - Brooker, Michael R.; D'Ambrosio, Jessica; Jones, Mackenzie M. L.; Kalcic, Margaret; King, Kevin W.; LaBarge, Greg; Panchalingam, Thadchaigeni; Roe, Brian E.; Schwab, Elizabeth R.; Soldo, Cole; Stoltzfus, Nathan D.; Wilson, Robyn S.; et al. (Frontiers in Sustainable Food Systems, 2021)
Legacy nutrients stored in agricultural soils are a substantial component of riverine nutrient discharge contributing to the eutrophication of aquatic ecosystems. These nutrient loads can persist and delay water quality initiatives, for example, those of the Great Lakes Water Quality Agreement which seek to reduce phosphorus (P) loads entering the Western Lake Erie Basin. In this watershed, approximately 5% of fields have P concentrations 2.5-fold greater than the maximum agronomic recommendations for corn and soybeans. Fields with these elevated-P concentrations (>100 mg P kg−1 soil) act as a source of legacy-P and discharge greater P loads. Implementing best management practices to treat runoff from these fields is desirable but finding them has been a challenge as soil test data are proprietary information creating an asymmetric information barrier. To overcome this barrier, we formed a public-private partnership that included agricultural retailers who conduct soil testing for farmers. Agricultural retailers who partnered with this project provided their soil P data and contacted farmers to gauge their interest, maintaining privacy for farmers until they expressed interest. Only 3.8% of soil samples in the provided data had elevated-P concentrations. In many cases, these elevated-P soils were confined to zones within fields, and 13% of fields had at least one elevated-P zone. We pursued these elevated-P fields as research sites for the implementation and monitoring of management practices. The agricultural retailers contacted 77 farmers with surveys, and 25 responded with interest in meeting the research team to discuss the project. Following a preliminary evaluation with the spatial data of fields operated by interested farmers, visits were arranged so that 12 research sites could be located. As indicated through the surveys, discussions with farmers, and soil data, many of the fields had accumulated elevated-P due to historic land-use (livestock, manure, or biosolid application) creating legacy sources. We conclude that public-private partnerships featuring agricultural retailers are a promising tool that may help overcome asymmetric information barriers to finding and managing agricultural fields with legacy-P that that disproportionately contribute to nutrient runoff.